Inflammatory fibrous hyperplasia: a rare case in a child - Carla Vânia de Oliveira FIGUEIREDO; Ana Flávia Bissoto CALVO; Auremir Rocha MELO; José Carlos Pettorossi IMPARATO (Faculdade São Leopoldo Mandic, 2019)
This paper aims to describe an inflammatory fibrous hyperplasia case caused by chronic irritation due to poor dental positioning after trauma. An 11-year-old female patient was sent to a dental specialty center with the complaint of a soft tissue growth in the place of an unerupted maxillary central incisor, causing her behavioral changes becoming more timid. After anamnesis and clinical examination it was noted that tooth 11 was in a vestibular position, covered with a hyperplastic lesion. Surgical treatment was performed and the histopathological exam revealed inflammatory fibrous hyperplasia. Over the course of the follow-up appointments, it was possible to observe improvement on the mentioned tooth and the patient's satisfaction. In face of the low prevalence of inflammatory fibrous hyperplasia, it is worth mentioning that the tooth positioning, outside its correct alignment in the arch, can cause repeated trauma to the mucosa, and then turning into etiological factor to inflammatory fibrous hyperplasia, affecting even children and adolescents. Thus, the dentistry must be alert to establish a diagnosis and clinical treatment, in addition to monitoring these cases.